Pendampingan Pembelajaran Matematika Inklusif melalui Pembelajaran Kooperatif dan Peer Tutoring Berbasis Pendekatan Psikologis, Manajemen Kelas, dan Kolaboratif : Pengabdian - Bhennita Sukmawati; Khusna Yulinda Udhiyanasari; Mochammad Maulana Trianggono; Neviyani Neviyani; I Wayan Eka Mahendra; Novalita Taufika Ilma; Moh. Aditiya Peratama (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to support inclusive mathematics learning through the implementation of cooperative learning and peer tutoring supported by psychological, classroom management, and collaborative approaches. The mentoring was conducted in October 2025 at SDN Mangli 1, Kaliwates District, Jember Regency, in third-grade mathematics learning involving regular students and students with special needs, namely dyslexia and slow learners. The methods used included coordination with the school and class teacher, observation, interviews, and documentation as a basis for reflection and improvement of learning. Cooperative learning was carried out through small heterogeneous groups, while peer tutoring involved regular students as peer tutors. The mentoring also emphasized inclusive classroom management and psychological support to increase student motivation, self-confidence, and social interaction. The results of the activity showed increased student engagement, understanding of the concept of arithmetic operations for students with special needs, the creation of a more inclusive and collaborative classroom atmosphere, and increased teacher experience in managing inclusive mathematics learning in a more structured and responsive manner.